Funções no ensino médio: uma abordagem conceitual e o uso de gamificaç - Camargo Júnior, Itamar de (2024)
In this paper we present a discussion about the manner how the concept of functions is approached in high school and discuss the teaching possibilities for this topic through gamified tasks in order to promote learning opportunities in Mathematics. It is a qualitative study and it is also classified as an applied research due to its goal. We bring a literature review about functions and gamification and as the research instruments we utilized two questionnaires. They were applied to both teachers and students from the 1st year of high school with the purpose of knowing their perceptions about the teaching and learning of functions the methodological approach adopted by the teachers and the textbook, the main difficulties of the students, and the vision of both parties in relation to new approaches to teaching and gamification We elaborated a didactic sequence composed by diagnostic and formative evaluation, directed study, theoretical lessons with contextual background and concepts, and practical lessons through a gamified task created on the digital platform Scratch. We realize the importance of caring about the concepts and the relevance of methodologies that enhance learning and provide new opportunities, all of which promote favorable learning environments for the teaching of Mathematics. We infer that there is potential in utilizing digital tools in teaching and learning, associated with the strictness of the concepts, which makes it possible to have a promising scenario for the teaching of Mathematics in Basic Education.